A tale of two signals: Global and local influences on the Late Pleistocene loess sequences in Bulgarian Lower Danube. (15th December 2021) - Fenn, Kaja; Thomas, David S.G.; Durcan, Julie A.; Millar, Ian L.; Veres, Daniel; Piermattei, Alma; Lane, Christine S.
Abstract: In Central and Eastern Europe, research has been focused on loess associated with a plateau-setting, which preserves distinct and well-developed loess and palaeosol units linked to orbital scale changes. This has led to the view that during the last glacial period the Middle and Lower Danube predominantly experienced dry continental climates and supported steppic environments. However outside of the typical plateau setting, some authors have reported a presence of embryonic palaeosols within loess units suggesting sufficient moisture for short-term pedogenesis, and therefore either large scale moisture delivery systems and/or influence of local climatic and/geomorphic factors. Here the palaeoenvironmental and palaeoclimatic history is reconstructed based on two loess-palaeosol profiles in Slivata, North Bulgaria. The site is located in proximity to both the Carpathian and Balkan Mountains and rest on the Danube river terrace. To understand the timing of sediment deposition and dust fluxes chronological approaches combining quartz optically stimulated luminescence (OSL), feldspar post infrared-infrared stimulated luminescence (pIR-IRSL), and tephra correlation were applied. The results are coupled with high-resolution particle size and magnetic susceptibility analysis to provide an overview of past environmental conditions at the site. Finally, zircon U–Pb ages are used to understand potential changes to sediment delivery patterns, in the context of the site development. The investigated profile at Slivata 2 preserves a loess-palaeosol record spanning 52–30 ka, with a very complex sedimentary sequence that switches between periods of enhanced dust flux and sediment accumulation, and palaeosol development. The Slivata 2 sequence is also punctuated by multiple thin "palaeosol" like units that are interpreted as colluvial "soil" deposits on the basis of sedimentology, provenance, and geochronology, indicating a highly variable and dynamic landscape responding to the surrounding environment. The chronology shows very rapid sediment accumulation at Slivata 1 during LGM, with mass accumulation rates similar to sites in the Carpathian Basin, suggesting strong winds and high sediment supply rates. Yet LGM loess is punctuated by a thin palaeosol, which developed between 20–19 ka. This coincides with a temporary glacial retreat in the Carpathian Mountains and higher moisture availability in Eastern Carpathians, and therefore points to localised influences on loess-palaeosol development. Moreover data from Slivata 1 shows soil development and by extension landscape and climate stabilisation shortly prior to 14 ka. The pre-Holocene onset of pedogenesis at Slivata supports ecological and glacial evidence of weak Younger Dryas from the South Carpathian Mountains. Lastly this paper provides a geochemical analysis of the thin tephra horizon preserved in the Slivata 2 profile, which was correlated to the Cape Riva/Y-2 tephra. Consequently Slivata is the most northerly terrestrial site found to contain this tephra horizon, which has implications for the understanding of the size of the Santorini's Cape-Riva/Y-2 explosion. The identification of the Cape Riva (Y-2) tephra horizon and new remodelled age of 21.92 ± 0.56 cal ka BP provides a new tephrostratigraphic marker for eastern European LGM loess. Highlights: Over short distances local factors including topography and proximity to mountain belts influenced loess profile variability. Provenance and chronological results show a minor switch in the sediment delivery mode and/or source between MIS2 and MIS3. The most northerly terrestrial site containing the Cape Riva/Y-2 tephra provides a new tephra marker for Danubian loess. First application of single grain zircon U–Pb dating as a tool for understanding depositional history of Lower Danube loess.